Synthesis, Characterization and Biocidal Study of Transition Metal Complexes of Schiff Base Derived from 2-Hydroxynaphthaldehyde - Saxena, Bharti; Sahai, V.M. (Asian Journal of Chemistry, 2012)
In the present work, we have synthesized some transition metal complexes of a Schiff base derived from 2-hydroxynaphthaldehyde. The structures of the new chelates were established by analytical and spectral data. Some of the metal chelates were found active against selected bacteria and fungi.